If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -2 = 18x + -4 Reorder the terms: -2 + 20x = 18x + -4 Reorder the terms: -2 + 20x = -4 + 18x Solving -2 + 20x = -4 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -2 + 20x + -18x = -4 + 18x + -18x Combine like terms: 20x + -18x = 2x -2 + 2x = -4 + 18x + -18x Combine like terms: 18x + -18x = 0 -2 + 2x = -4 + 0 -2 + 2x = -4 Add '2' to each side of the equation. -2 + 2 + 2x = -4 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -4 + 2 2x = -4 + 2 Combine like terms: -4 + 2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 6-3(3x-3)=6 | | 2(5-x+10)=9 | | -6a-4(-8a+2)=-a-8 | | x^2=-100 | | X-0.25x+25=231.25 | | 6(6x-6)=18x | | ln(x)+ln(x+2)=4 | | -16t^2-28t+250=0 | | 1.6n+0.8=(n+10)(0.7)+0.1 | | 3x^2+6x+15=0 | | -5x-7=9x+21 | | 2(-m+7)+m=16-3m | | -16t^2-28x+250=0 | | 7(y-2)/5=-4y | | 4y-2n=9 | | 4x^2+10x=-10x-25 | | 1.8a-5=-2.3 | | 8x^2+11x+3= | | 36+b=6(-2n-4)+b | | 3(7x+1)=9-3(x-4) | | 2x^2-3=-93 | | 6n^2+17n+7= | | 15x=72 | | 5.3x-2.68=2.12-6.7x | | 1.2x-1.7-2.1x=-1.9x-2.6 | | b^2+5b-50= | | n^2-8n-20= | | 3.5-2x=x+7.5 | | p^2+6p-7= | | 7.6x-3.5x=-65.6 | | 11x+8-4=10x-3 | | k^2-16k+60= |